Isothermal Pyrolysis Kinetics of Various BiomassTypes using Thermogravimetric Data - Andini Hizbiyati; Hendriyana (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2025)
Biomass is a renewable fuel source that can be converted into bio-oil as an alternative energy source. The type of biomass with the potential to produce bio-oil is rice husks, water hyacinths, and corn cobs. This study was conducted to examine manufacture of bio-oil from various biomass using the pyrolysis method using a variety of several variables, including operating temperature (450oC and 550oC), particle size (-2 mm/+1 mm and +2 mm), and type of biomass. It was observed that corn cobs yielded the highest output with 49.06% with a size of +2 mm at an operating temperature of 450oC. The preparation of kinetic models is carried out by observing changes in mass per unit of time. The kinetic model approach using the order of 1/3 is able to produce values that are almost close to the research data. The results of kinetics model preparation obtained energy value of activation of the pyrolysis process for rice husks, which ranges from (24.55 – 27.79) kJ/mol, for corn cobs ranging from (35.51 – 42.55) kJ/mol, for water hyacinths with leaves ranging from (23.55–30.72) kJ/mol, for water hyacinths with stems ranging from (30.11–46.77) kJ/mol, and for mixed water hyacinths ranging from (35.72–40.70) kJ/kmol.